KERAGAAN AGROINDUSTRI MI BASAH DI KOTA BANDAR LAMPUNG DAN PERILAKU KONSUMEN DALAM PERSPEKTIF DIVERSIFIKASI PANGAN - Yohana Julina Sinaga; Dyah Aring Hepiana Lestari; Suriaty Situmorang (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
The purpose of this research are to analyze the procurement process of raw materials on six precision (on time, right place, right quality, right quantity, right type, and right price), processing activities to earn income and create added value of products, distribution channels in product marketing activities, the roles of supporting services, and consumer behavior of wheat flour and wet noodle. This research uses a case study method at Multi Sari 99 Agroindustry in Panjang District, Bandar Lampung City. Data were collected in January – April 2018 and analyzed descriptively using quantitative and qualitative analyses. The results of this research showed that the six components of raw materials procurement process of Multi Sari 99 Agroindustry had been done precisely. The income earned by Multi Sari 99 Agroindustry was Rp2,009,349.54/100 kg wheat flour. Mi Basah Multi Sari 99 Agroindustry was considered viable since it had possitive added value and profitable as R/C ratio value was more than one. There were two channels in marketing activities of wet noodle product. Supporting services utilized by the agroindustry had given positive impacts toward agroindustry activities. Wheat flour consumers and wet noodles consumers did not understand about food diversification program. Consumers would still consume wet noodles even though they know that the raw materials are imported.Key words : agroindustry, consumer, performance, wet noodle